2020
DOI: 10.1016/j.watres.2020.115586
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity, ecological networks and functional traits associated to materials used in drinking water distribution systems

Abstract: Drinking water distribution systems host complex microbial communities as biofilms that interact continuously with delivered water. Understanding the diversity, behavioural and functional characteristics will be a requisite for developing future monitoring strategies and protection against water-borne health risks. To improve understanding, this study investigates mobilisation and accumulation behaviour, microbial community structure and functional variations of biofilms developing on different pipe materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…This is in agreement with other studies where fungal communities in drinking water biofilms tended to be less diverse and more stable over time 73 when compared with bacteria. From this study, we can confirm that fungi formed part of mix-species consortia with bacteria in biofilms, being an important component of the microbial communities of lead and PVC materials in DWDS 73,74 . Despite fungi are not usually included in drinking water regulations, the monitoring of these organisms should be considered by water utilities due to their involvement in processes that can deteriorate water quality.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This is in agreement with other studies where fungal communities in drinking water biofilms tended to be less diverse and more stable over time 73 when compared with bacteria. From this study, we can confirm that fungi formed part of mix-species consortia with bacteria in biofilms, being an important component of the microbial communities of lead and PVC materials in DWDS 73,74 . Despite fungi are not usually included in drinking water regulations, the monitoring of these organisms should be considered by water utilities due to their involvement in processes that can deteriorate water quality.…”
Section: Discussionsupporting
confidence: 61%
“…Bacteria belonging to the genera Sphingomonas, Afipia and Acidovorax, and fungal genera such as Exophiala, Cadophora and Fusarium, were detected in all the conditions and materials studied. It can be suggested that these microorganisms form a core community and play a key role in biofilm formation, as proposed by other researchers studying mixed-species biofilms [72][73][74][75][76][77] . In these studies, bacteria belonging to the genera Acinetobacter, Burkholderia, Methylobacterium, Mycobacterium, Sphingomonas and Staphylococcus played an important role in the formation of biofilms an aggregates [78][79][80][81] .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…More than 98% of the total biomass present in DWDS have been found to be present as biofilms and loose deposits in an unchlorinated DWDS as quantified by adenosine triphosphate (ATP) analysis and DNA-pyrosequencing (Liu et al 2014). There is limited access to operating water main pipes and hence, most prior studies have been conducted on premise plumbing systems including i) mature pipe biofilms in buildings designated to be demolished (Henne et al 2012), ii) biofilms within replaced water meters (Ling et al 2016), and iii) young sentinel biofilms growing on carrier coupons in model systems (Douterelo et al 2014) or fire hydrant outlets (Douterelo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To address this difficulty, studies have investigated different types of biofilms in the DWDS that are more accessible, including biofilm on water meters 8 and coupons recovered from pilot-and full-scale systems, 9,10 as well as estimations of the biofilm community by sampling water at different locations in the DWDS. 11,12 Grab samples of pipe biofilm, obtained for research purposes or during pipe maintenance, have also been investigated. 1,8,[13][14][15] Maintaining disinfectant residuals such as chloramine to repress growth of problematic organisms in the DWDS is common practice.…”
Section: Introductionmentioning
confidence: 99%